Effects of menstruation and contraceptive pill on the performance of physical education students. Issue 1 (March 1983) - Bale, P.; Davies, J.
Abstract : Of the 109 specialist female physical education students who answered a detailed questionnaire on menstruation and the contraceptive pill in relation to exercise, 91 (83.5%) reported that they suffered menstrual problems. These included stomach ache, depression, abdominal cramps and backache. Over two-thirds of the students considered that these problems adversely influenced their physical performance. However, whether they had a mainly physiological or psychological effect is not clear. Many of the students with menstrual problems thought that exercise had a beneficial effect and helped alleviate their discomfort. A small number of students reported problems such as amenorrhoea and reduced menses possibly due to excessive training. Just under half the students in the investigation took the contraceptive pill, and though as many students taking the pill complained of menstrual problems as those not taking it, they reported less problems and to a lesser degree. Most students claimed that taking the contraceptive pill had no effect upon their performance.